2017
DOI: 10.18203/2319-2003.ijbcp20173754
|View full text |Cite
|
Sign up to set email alerts
|

Dental students’ perceptions and feedback on teaching and learning pharmacology

Abstract: Background: There is a shift in the teaching learning process with the advent of newer methodologies. The present study was conducted to obtain feedback from 2 year dental students regarding teaching and learning methodology and their perception about pharmacology.Methods: This was an observational, cross-sectional questionnaire based survey. A self-designed questionnaire containing 10 questions with 4-6 options regarding the teaching and learning methodology was given to 2nd year dental students. Responses wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…This result may be related to the traditional lecture-based teaching method, which does not optimize the assimilation of pharmacotherapy concepts [20]. Some studies reported that dental scholars signi cantly improved their prescribing skills after receiving interactive classes in pharmacology [21,22]. Debating in the classroom seems to be an effective learning method since it improves the level of cognitive skills and the use of scienti c databases regarding several topics such as the use of water uoridation for drinking purposes as well as the use of antibiotics in dentistry [23].…”
Section: Discussionmentioning
confidence: 99%
“…This result may be related to the traditional lecture-based teaching method, which does not optimize the assimilation of pharmacotherapy concepts [20]. Some studies reported that dental scholars signi cantly improved their prescribing skills after receiving interactive classes in pharmacology [21,22]. Debating in the classroom seems to be an effective learning method since it improves the level of cognitive skills and the use of scienti c databases regarding several topics such as the use of water uoridation for drinking purposes as well as the use of antibiotics in dentistry [23].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is an agreement that the quality of instructors, assessment type, learning environment and lecture content influence overall learning for dental students. 17,[35][36][37][38][39][40][41][42] Furthermore, it is important to emphasise that supervising tutors may need additional training to ensure that they are competent in the knowledge of modern prescribing frameworks and that they understand the principles of antimicrobial stewardship and the quality use of medicines. 9,43 The current study had several strengths and limitations worth noting.…”
Section: Discussionmentioning
confidence: 99%
“…It serves as a foundation stone for clinical practice. 1 Currently teaching of pharmacology in the medical curriculum especially in India is primarily drug-centred and imparts factual knowledge instead of therapeutic skills. 2 As opposed to traditional and passive didactic lectures, active-learning strategies address the educational content in an interactive learning environment to develop interpersonal, communication, and problem-solving skills needed by future doctors to function effectively in their new roles.…”
Section: Introductionmentioning
confidence: 99%